Repositioning Nigeria’s Amnesty Programme for Conflict Transformation and Post-Conflict Peace-Building in the Niger Delta Region of Nigeria (Singaporean Journal of Business Economics and Management, 2013)
One of the latest attempts to effectively manage the crisis in the Niger Delta region of Nigeria was the declaration of amnesty for all militants in the region by the late President of Nigeria, Umaru Musa Yar’Adua, on the 25th of June, 2009. The death of the President did not bring an end to the amnesty programme as a core Niger Delta man, Goodluck Jonathan, became Nigeria’s president and has continued with the amnesty programme. This study seeks to examine the contexts, contents and challenges of the amnesty programme with a view to establishing the nature of peace it has achieved in the region, the nexus between the performance of the amnesty programme and the structure of the Nigerian state, and how the amnesty programme can be used for conflict transformation and postconflict peace-building in the Niger Delta region. Primary and secondary sources of data collection were used for this work. The primary sources were In-depth Interviews (IDIs) with some ex-militants and some members of the ex-militants’ communities and Camp Officials. Key Informant Interview (KII) was also used. Secondary sources include relevant books, journals, and other publications on Niger Delta. Qualitative method was used for data analysis. The study argues that a mere declaration of an amnesty, without correspondent actions by the state to remove structural forms of violence that have sustained the crisis in the region, as well as embarking on a radical infrastructural and socioeconomic development of the region, will lead to the collapse of the relative peace in the region. It further posits that Nigeria’s amnesty programme is capable of bringing lasting peace to the region and the nation as a whole if, and only if, a holistic approach that will take the structure of the Nigerian federalism is taken into consideration. That is, the evolvement of true federalism and the abrogation of all laws that are used to subdue, oppress, and deprive the people of the region from benefiting maximally from the Nigerian commonwealth. It is only when these are done that a genuine transformation of the actors, issues, rules, and structures in the crisis will be achieved in the Niger Delta of Nigeria.